Ventilation in pumped storage power stations: Influence of dehumidifiers in an underground tunnel. (25th May 2020) - Xue, Feifei; Xu, Chang; Shen, Wenzhong; Li, Linmin
Highlights: A field test in a tunnel with dehumidifiers operating was carried out. A new model to calculate temperature decrease for tunnels was proposed. Comparison between data with dehumidifiers and historical data. Temperature and humidity inside of the underground tunnel were analyzed. Dehumidification efficiency influenced by the dehumidifiers and entrance temperature. Abstract: The underground tunnel is of key importance to the ventilation in a pumped storage power station (PSPS). The heat and moisture environment of PSPS directly affects the operation safety of electrical equipment and the health of workers. The present work aims to analyze the influence of industrial dehumidifiers in the traffic tunnel on the ventilation performance. A field test in a PSPS was carried out, and the results showed that the temperature of the overall traffic tunnel decreases no longer in an exponential mode as compared with that without industrial dehumidifiers. A new model to predict the temperature decrease is proposed for tunnels, and the results of the new model are in good agreement with the test results. The industrial dehumidifiers can control the relative humidity to meet the requirements, and the average outlet temperature is found 3.85 °C higher than the historical data. The higher entrance temperature gives the higher stable value of cooling efficiency at the outlet of traffic tunnel, and the higher relative humidity of the entrance gives the higher relative humidity of the outlet. Under the similar entrance temperature in the traffic tunnel, the dehumidification efficiency reaches approximate value at the outlet. Meanwhile, dehumidification efficiency can be enhanced by an average of 7%–9% with TC increased 2 °C.